2001
DOI: 10.1016/s0014-5793(01)02210-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro glucuronidation of xanthohumol, a flavonoid in hop and beer, by rat and human liver microsomes

Abstract: Xanthohumol (XN) is the major prenylated flavonoid of hop plants and has been detected in beer. Previous studies suggest a variety of potential cancer chemopreventive effects for XN, but there is no information on its metabolism. The aim of this study was to investigate in vitro glucuronidation of XN by rat and human liver microsomes. Using high-performance liquid chromatography, two major glucuronides of XN were found with either rat or human liver microsomes. Release of the aglycone by enzymatic hydrolysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 18 publications
6
99
0
1
Order By: Relevance
“…The bioavailability of xanthohumol has not yet been completely elucidated. Yilmazer et al reported the metabolism of xanthohumol using rat and human microsomes 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The bioavailability of xanthohumol has not yet been completely elucidated. Yilmazer et al reported the metabolism of xanthohumol using rat and human microsomes 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The major chalcone xanthohumol, as well as the flavanones isoxanthohumol, and 6PN and 8PN show various forms of antioxidant activity in vitro in the micromolar range, and are weakly cytotoxic to certain cancer cell lines (Gerhäuser et al, 2001a;Gerhäuser et al, 2001b;Milligan et al, 1999;Miranda et al, 2000a;Miranda et al, 2000b). In addition, the metabolism of prenylated chalcones and flavanones from hops in vitro and in vivo has been investigated (Nikolic, 2004;Nookandeh, 2004;Yilmazer, 2001aYilmazer, , 2001b.…”
Section: Other Activitiesmentioning
confidence: 99%
“…In contrast to many other chalcones, the metabolism of XN was extensively studied, and both in vitro and in vivo studies have been conducted (Hanske et al, 2010;Henderson et al, 2000;Yilmazer et al, 2001aYilmazer et al, , 2001b. These studies have revealed, that on the one hand XN is a potent inhibitor of P450 enzymes (Henderson et al, 2000), but on the other hand it is also heavily metabolized by liver cells (Hanske et al, 2010;Nikolic et al, 2005) and microorganisms (Kim and Lee, 2006;Nookandeh et al, 2004) into several other, prenylated and non-prenylated chalcones.…”
Section: Introductionmentioning
confidence: 99%